Psychological approaches to the development of professional technical thinking of vocational school students (Pedagogy of Higher and Secondary Education, 2011)
Theoretical survey and analysis of scientific literature about professional thought developing in up-to-date psychology, psychological ad pedagogical fundamentals of mining trade schools students thinking are discussed and characterized in the article
Keywords: professional thinking; technical thinking; technical creative activity; mining trade schools; educational problems of professional direction solving